CSF beta‐amyloid levels are altered in narcolepsy: a link with the inflammatory hypothesis?. (19th February 2014) - Liguori, Claudio; Placidi, Fabio; Albanese, Maria; Nuccetelli, Marzia; Izzi, Francesca; Marciani, Maria Grazia; Mercuri, Nicola Biagio; Bernardini, Sergio; Romigi, Andrea
Summary Narcolepsy is characterized by hypocretin deficiency due to the loss of hypothalamic orexinergic neurons, and is associated with both the human leucocyte antigen DQB1*06:02 and the T cell receptor polymorphism. The above relationship suggests autoimmune/inflammatory processes underlying the loss of orexinergic neurons in narcolepsy. To test the autoimmune/inflammatory hypothesis by means of cerebrospinal fluid (CSF) levels of beta‐amyloid1–42 and/or total tau proteins in a sample of narcoleptic patients, we analysed 16 narcoleptic patients and 16 healthy controls. Beta‐amyloid1–42 CSF levels were significantly lower in narcoleptic patients compared with healthy controls. We also documented pathologically low levels of CSF beta‐amyloid1–42 (<500 pg mL−1) in six of 16 narcoleptic patients (37.5%). We hypothesize that the significant decrease of the CSF beta‐amyloid1–42 levels in narcoleptic patients may support both the inflammatory/autoimmune hypothesis as the basis of the pathogenesis of narcolepsy and the prevalence of an 'amyloidogenic' pathway caused by the deficiency of the alpha‐secretases enzymes.